Development of Kras mutant lung adenocarcinoma in mice with knockout of the airway lineage‐specific gene Gprc5a. Issue 8 (17th July 2017) - Fujimoto, Junya; Nunomura‐Nakamura, Sayuri; Liu, Yihua; Lang, Wenhua; McDowell, Tina; Jakubek, Yasminka; Ezzeddine, Dalia; Kapere Ochieng, Joshua; Petersen, Jason; Davies, Gareth; Fukuoka, Junya; Wistuba, Ignacio I.; et al.
Abstract : Despite the urgency for prevention and treatment of lung adenocarcinoma (LUAD), we still do not know drivers in pathogenesis of the disease. Earlier work revealed that mice with knockout of the G‐protein coupled receptor Gprc5a develop late onset lung tumors including LUADs. Here, we sought to further probe the impact of Gprc5a expression on LUAD pathogenesis. We first surveyed GPRC5A expression in human tissues and found that GPRC5A was markedly elevated in human normal lung relative to other normal tissues and was consistently downregulated in LUADs. In sharp contrast to wild‐type littermates, Gprc5a –/– mice treated chronically with the nicotine‐specific carcinogen NNK developed LUADs by 6 months following NNK exposure. Immunofluorescence analysis revealed that the LUADs exhibited abundant expression of surfactant protein C and lacked the clara cell marker Ccsp, suggesting that these LUADs originated from alveolar type II cells. Next, we sought to survey genome‐wide alterations in the pathogenesis of Gprc5a –/– LUADs. Using whole exome sequencing, we found that carcinogen‐induced LUADs exhibited markedly higher somatic mutation burdens relative to spontaneous tumors. All LUADs were found to harbor somatic mutations in the Kras oncogene (p. G12D or p. Q61R). In contrast to spontaneous lesions, carcinogen‐induced Gprc5a –/– LUADs exhibited mutations (variants and copy number gains) in additional drivers ( Atm, Kmt2d, Nf1, Trp53, Met, Ezh2 ). Our study underscores genomic alterations that represent early events in the development of Kras mutant LUAD following Gprc5a loss and tobacco carcinogen exposure and that may constitute targets for prevention and early treatment of this disease. Abstract : What's new? The development of Kras ‐mutant lung adenocarcinoma (LUAD), the most common molecular subtype of lung cancer, is poorly understood. Previous research, however, implicates Gprc5a, a retinoid‐inducible G‐protein coupled receptor, in the emergence of late‐onset LUAD. Using in vivo carcinogenesis models and whole‐exome sequencing, this study shows that Gprc5a –/– mice develop spontaneous LUADs with somatic driver Kras mutations. Gprc5a –/– mice exposed to the tobacco carcinogen NNK experienced accelerated development of LUADs harboring co‐occurring mutations in additional drivers that potentially cooperate with Kras to facilitate LUAD pathogenesis. These additional drivers may be viable targets for early therapeutic intervention in Kras ‐mutant LUAD.